Access to Financial Services in Colombia : The “Unbanked” in Bogotá - Solo, Tova Maria; Manroth, Astrid (World Bank, Washington, DC, 2012)
The authors look at the depth of the financial sector in Bogota in terms of the "financial exclusion" of those, particularly poorer citizens, who operate without accounts in formal financial institutions-the unbanked. They begin with a review of the overall decline in financial intermediation from 1998 to 2003, which explains, in part, the high percentage of unbanked-61 percent in a recent household survey in Bogota. The authors next look at the banking system today, concluding that the present challenge is to increase financial intermediation overall, especially with the poor. Their analysis shows that Colombia's banks provide costly services mainly catered toward high-income clients. Existing fees and costs of checking, savings, and loan services average 5-10 percent of a monthly minimum wage, making them hard to afford for low-income clients. The authors also explore the characteristics and impacts of financial exclusion associated with lower and more uncertain incomes, lower education, and closer links to the informal sector. They cite the household survey conducted in Bogota, showing that 70 percent of the unbanked earn less than one minimum wage per month, are three times more likely to be unemployed than the banked, and have lower education levels. The unbanked save and borrow largely in the informal sector, at greater risk and greater cost. At the same time, however, high home ownership rates show that the unbanked have the capacity to build assets, demonstrating that they have "bankable" characteristics. The authors conclude with recommendations for government and for the financial sector to broaden access for the benefit of public and private sectors, and for the unbanked.